Meningkatkan Kemandirian Belajar Siswa Materi Mengembangkan Budaya Kasih Dengan Metode PBL Kelas XI SMKN 1 Singkawang - Ratnawati Ratnawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Students who are accepted at SMK Negeri 1 Singkawang are not all in accordance with their main choice, causing low learning independence and learning achievement, so they do not reach the KKTP of 75. This study aims to: 1) Knowing the increase in learning independence in the material of developing a culture of love class XI at SMK Negeri 1 Singkawang. 2) Knowing the effectiveness of the PBL method in improving student learning outcomes in the material of developing a culture of love class XI at SMK Negeri 1 Singkawang. This research applies a quantitative descriptive approach, namely making descriptions of a situation objectively using numbers, starting from data collection, interpretation and appearance of the results. The research design is Classroom Action Research conducted in two (2) cycles, on class XI students with a population of 8 people. The results showed that 1) PBL can increase learning independence in the material of developing a culture of love class XI at SMK Negeri 1 Singkawang. It can be seen that the average independence from 69.94 increased to 78.87%. 2) PBL is effective in improving the achievement of student learning outcomes in the material of developing a culture of love class XI at SMK Negeri 1 Singkawang. It can be seen that proficient 0%, feasible 66.67% and proficient 33.33%, increased to proficient 66.67%, feasible 16.67% and proficient 16.67%. Thus, it can be concluded that the PBL method is effective in increasing independence and learning achievement.